The Potential and Role of the Traditional Village in the Development of Sangeh Tourism Village as a Tourism Destination Area - I Wayan Putu Sucana Aryana; Benyamin Tungga; I Made Oka; Ketut Ngurah Arjaya; I Gusti Anom Gumanti; I Ketut Suastika; Rizal Syah Nyaman; Gusti Ngurah Arya Surya Diatmika; I Made Sutapa; I Made Karyadha; I Wayan Mustika (Fakultas Hukum, Universitas Warmadewa, 2023)
Bali has various tourism potentials both natural and cultural which yet to be explored and identified further in order to be developed to become tourist attractions, with feasible facilities available that can be offered. Sangeh Village is one of tourist villages in Badung Regency which has various tourism potentials and one of it is Tourist Attraction of Alas Pala Sangeh. In addition there are still many other tourism potentials which are yet to be developed and promoted optimally. Therefore this research was conducted to identify tourism potentials existed at Tourist Village of Sangeh. The method being used in this research was qualitative method with data sampling technique through observations, in depth interviews, and literature studies so that able to identify tourism potentials existed at Tourist Village of Sangeh. The result of this research shows that the Village of Sangeh is one of customary villages in Bali which has various tourism potentials so that the Village of Sangeh is called a Tourist Village. The potentials owned by Tourist village of Sangeh is in the form of physical and non-physical potentials. Physical potentials referred to among others are Tourist Garden of Mumbul, Tourist Attraction of Alas Pala Sangeh and Pondok Jaka, whereas non-physical potential is Trekking activity managed by POKDARWIS Bukit Sari Sangeh, an institution that supervise Sangeh Traditional Activity.This research aims to identificate potentials of tourism available in Tourist Village of Sangeh.